Do Macroeconomic and Green Factors Influence Stock Returns in Indonesia? - Irman, Mimelientesa; Rahman, Sarli; Wati, Yenny (ETIKONOMI, 2025)
Research Originality: This study adopts a multidimensional framework that integrates environmental sustainability and macroeconomic pressures to assess stock market behavior over the period 2018 to 2022, encompassing both pre-pandemic and post-pandemic economic contexts. Research Objectives: This research explores the impact of inflation, economic growth, green accounting, and environmental performance on stock returns of energy companies registered on IDXENERGY from 2018 to 2022. Research Methods: This study uses panel data regression analysis based on secondary data from 33 energy sector companies over five years. Empirical Result: Inflation has a statistically significant negative effect on stock returns, indicating that rising inflation tends to reduce investor returns in the energy sector. In contrast, economic growth, green accounting, and environmental performance do not show significant effects on stock returns, suggesting that these variables have no observable impact on firm performance in the capital market within the scope of this study. Implications: The findings emphasize the need for enhanced green reporting standards, stronger policy incentives for sustainable practices, and increased investor awareness regarding environmental performance. JEL Classification: E31, O47, M41, Q56, G12